Table1_Spinel Harzburgite-Derived Silicate Melts Forming Sulfide-Bearing Orthopyroxenite in the Lithosphere. Part 1: Partition Coefficients and Volatile Evolution Accompanying Fluid- and Redox-Induced Sulfide Formation.XLSX - A. Bénard; C. Le Losq; O. Müntener; M. Robyr; O. Nebel; R. J. Arculus; D. A. Ionov (2022)
We report abundances of major trace and volatile elements in an orthopyroxenite vein cutting a sub-arc, mantle-derived, spinel harzburgite xenolith from Kamchatka. The orthopyroxenite contains abundant sulfides and is characterized by the presence of glass (formerly melt) both interstitially and as inclusions in minerals, comparable with similar veins from the West Bismarck arc. The glass formed by quenching of residual melts following crystallization of abundant orthopyroxene, amphibole, and minor olivine and spinel. The interstitial glass has a low-Ti, high-Mg# andesite composition, with a wide range of H 2 O and S contents but more limited F and Cl variations. We calculate trace element partition coefficients using mineral and glass data, including those for halogens in amphibole, which agree with experimental results from the literature. Despite having a similar, high-Mg# andesite composition, the orthopyroxene-hosted glass inclusions usually contain much more H 2 O and S than the interstitial glass (4–7 wt% and ∼2,600 ppm, respectively). The initial vein-forming melts were oxidized, recording oxygen fugacity conditions up to ∼1.5 log units above the fayalite–magnetite–quartz oxygen buffer. They intruded the sub-arc mantle lithosphere at ≥1,300°C, where they partially crystallized to form high-Mg# andesitic derivative melts at ca. 1,050–1,100°C. Comparison with literature data on glass-free orthopyroxenite veins from Kamchatka and the glass-bearing ones from West Bismarck reveals fundamental similarities indicating common parental melts, which were originally produced by low-degree melting (≤5%) of spinel harzburgite at ≥1,360°C and ≤1.5 GPa. This harzburgite source likely contained ≤0.05 wt% H 2 O and a few ppm of halogens. Volatile evolution inferred from glass compositions shows that (i) redox exchange between S 6+ in the original melt and Fe 2+ in the host mantle minerals, together with (ii) the formation of an S-bearing, (H 2 O, Cl)-rich hydrothermal fluid from the original melt, provides the conditions ...